RANCANG BANGUN SISTEM PERHITUNGAN ORANG ATAU PENGUNJUNG DALAM SEBUAH RUANGAN BERBASIS ARDUINO - Rizal, Muhammad; Nopriadi, Nopriadi (LPPM Universitas Putera Batam, 2023)
This research aims to design and implement an Arduino-based system for counting and tracking people in SMK Tunas Baru Berkarya's auditorium. The system will use infrared sensors on the doors to detect visitors and Arduino as the central system to process the data. It will also control the doors using servo motors. The study will involve several stages, including selecting and configuring the infrared sensors, developing Arduino programs for visitor detection and counting, and adjusting the servo motors for door control. Testing and evaluation will ensure the system's reliability and effectiveness in monitoring room capacity and controlling door access based on available capacity. The research's outcomes are expected to benefit the auditorium management by optimizing room usage, enhancing visitor safety, and providing a seamless experience for visitors.